STAGES AND DIDACTIC CONDITIONS FOR ORGANIZING LESSONS IN LANDSCAPE DRAWING - Tursunova Dilshoda Jahongirovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
ANNOTATION: This article examines the stages and didactic conditions for organizing lessons in the landscape drawing genre. It analyzes pedagogical strategies, step-by-step lesson structuring, and classroom conditions that enhance students’ learning outcomes, artistic skills, and creative expression. The study emphasizes the importance of systematic lesson progression, practical exercises, and appropriate learning environments to ensure effective instruction in landscape drawing. The article also discusses methods for fostering students’ compositional understanding, spatial perception, and aesthetic awareness through carefully organized lessons.